Acute Ataxia in Children: Approach to Clinical Presentation and Role of Additional Investigations - Poretti, Andrea; Benson, Jane E.; Huisman, Thierry A. G. M.; Boltshauser, Eugen (Neuropediatrics, 2013)
Acute ataxia is a fairly common emergency that confronts the pediatric neurologist in daily life. The differential diagnosis of acute pediatric ataxia is wide, but informed history and careful clinical examination can narrow it and help target investigations. This review discusses various etiologies of acute pediatric ataxia, focusing on clinical presentation, diagnostic considerations, and approach to investigation. Aspects of treatment and prognosis are also mentioned. Diseases with potentially high morbidity and mortality, such as acute cerebellitis, opsoclonus-myoclonus syndrome, and cerebellar stroke, receive particular attention.
Keywords: acute ataxia; children; differential diagnosis; cerebellar ataxia; neuroimaging; acute cerebellitis